Confocal three-dimensional micro X-ray scatter imaging for non-destructive detecting foreign bodies with low density and low-Z materials in food products. (August 2015) - Li, Fangzuo; Liu, Zhiguo; Sun, Tianxi; Ma, Yongzhong; Ding, Xunliang
Abstract: Confocal three-dimensional (3D) micro X-ray scatter imaging technology based on polycapillary X-ray optics was used to carry out a point-to-point image analysis of foreign bodies in food products which were consisting of low density materials with low-Z elements. This confocal 3D micro X-ray scatter imaging method was based on a polycapillary focusing X-ray lens (PFXRL) in the excitation channel and a polycapillary parallel X-ray lens (PPXRL) in the detection channel. The PFXRL and PPXRL were placed in a confocal configuration. This let only the X-rays scattered from the confocal micro-volume overlapped by the output focal spot of the PFXRL and the input focal spot of the PPXRL be detected by the detector. The aim of this study was to demonstrate the ability of confocal micro X-ray scattering technology based on polycapillary X-ray optics to discriminate foreign bodies which adulterated in food products, and also utilize this confocal micro X-ray scattering technology to present scattered X-ray imaging for them. This confocal 3D micro-beam X-ray scattering imaging technology has potential applications in such fields as food safety, agriculture, bio-pharmaceutical, Meat Science, and so on. Highlights: Confocal X-ray scatter imaging was used for identifying foreign bodies in foods. This approach was based on differences of density of foreign bodies in foods. The confocal X-ray scattering technology was based on polycapillary X-ray optics. Point-to-point imaging for several foreign bodies in foods were obtained.